1995
DOI: 10.1111/j.1479-828x.1995.tb02146.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Work Activity in Pregnancy on the Risk of Severe Preeclampsia

Abstract: The aim of this study was to evaluate the impact of type of employment and level of physical activity at work on the risk of severe preeclampsia. For this purpose, we carried out a case control study of 160 nulliparous pregnant women with severe preeclampsia and 320 normotensive nulliparous controls who received prenatal care from members of one medical staff. The type of employment and the level of physical activity sustained at work were ascertained at birth through an interview based on a standard questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 23 publications
(19 reference statements)
0
39
0
1
Order By: Relevance
“…On the other hand, some authors have reported that employment during pregnancy is a significant risk factor for developing PE. 12,23 This difference may be due to a lesser number of employed women in both groups. The present population of Northern Nigeria women represents a group, among which most women are not formally employed, but may be working much harder in large joint families, which was a significant risk factor for severe early-onset PE (AOR 6.93).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, some authors have reported that employment during pregnancy is a significant risk factor for developing PE. 12,23 This difference may be due to a lesser number of employed women in both groups. The present population of Northern Nigeria women represents a group, among which most women are not formally employed, but may be working much harder in large joint families, which was a significant risk factor for severe early-onset PE (AOR 6.93).…”
Section: Discussionmentioning
confidence: 90%
“…9,10 The stress at work was calculated by a fivelevel activity score, based on the distance and transportation from home to workplace, type and physical intensity of work and weekly working hours adapted from a study by Anorlu et al 11 The nature of work among the employed women in the present study was classified into sedentary, moderate and intense physical activity. 12 Anorlu et al had calculated the stress at home in terms of lack of home help, number of young children, stress from husband and number of extended family members living with the patient. They assess factors regarding stress at home and its role as a risk factor in PE.…”
Section: Methodsmentioning
confidence: 99%
“…Venous insufficiency is thought to play a role in the relationship between occupational physical activity and fetal health (eg, growth retardation) 5,6 and preeclampsia. 7 Mechanical compression, altered venous tone, and poor venous return from the lower extremities may be exacerbated by constrained postural demands (eg, prolonged standing, stooping), inducing conditions of fetal hypoxia. Increased intraabdominal pressure has been hypothesized to explain significant associations between forward flexion of the upper body (or stooping) and preterm delivery 8 and spontaneous abortion.…”
Section: Occupational Lifting and Fetal-maternal Health Outcomesmentioning
confidence: 99%
“…24 Additionally, a 2-fold increased risk of preeclampsia was found for pregnant women with high physical activity at work (composite score). 7 An explanatory model by Paul et al 25 (1994) suggests that pregnancy-related musculoskeletal problems arise, at least in part, from reduced load-bearing capacity associated with joint laxity. Although the mechanisms underlying laxity are unknown, the condition presents early in pregnancy and persists beyond 6 weeks postpartum.…”
Section: Occupational Lifting and Fetal-maternal Health Outcomesmentioning
confidence: 99%
“…Ao contrário da actividade física no lazer, alguns estudos sugerem que a realização de tarefas fisicamente exigentes no trabalho durante a gravidez está associada a um aumento do risco de pré-eclâmpsia, parto pré-termo, reduzido tamanho para a idade gestacional e baixo peso à nascença (Croteau, Marcoux, & Brisson, 2006;Mamelle, Laumon, & Lazar, 1984;Henriksen, Hedegaard, Secher, & Wilcox, 1995;Spinillo et al, 1996;Spinillo et al, 1995). Por essa razão, apenas o exercício físico de intensidade ligeira a moderada é recomendado durante a gestação, na ausência de complicações obstétricas (ACOG, 2003;Davies, Wolfe, Mottola, & MacKinnon, 2003;Royal College of Obstetricians and Gynaecologists, 2006).…”
unclassified